Gamelan Bocah (GACAH): Penumbuhan Karakter Kebangsaan di TK Sari Asih Yogyakarta - Pamungkas, Joko; Syamsudin, Amir; Harun, Harun (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2018)
This study aims to describe the children gamelan media  in fostering national character values such as tolerance, responsibility, independence, adaptation, courtesy and discipline, and finalize the achievements of gross motoric development, fine motor skills, cognitive, and the early childhood art. This research method uses quasi-experiment. The variables consisted of playing children gamelan, children development, and national character values. The subjects were 16 students aged 4-6 years of Sari Asih Kindergarten, Catur Tunggal, Depok, Sleman, Yogyakarta. This research starts from learning using children gamelan media and observing children national character behavior as well as the achievements of the children development. Data collection techniques use observation sheets for national character behavior and unstructured interview guidelines. The data analysis technique uses descriptive-qualitative. The results showed that playing children gamelan can accelerate the stimulation of the values of tolerant, responsible, and children independent characters, and can finalize the achievement of gross and cognitive motor development.